2014
DOI: 10.1016/j.neuroimage.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

The Reference Ability Neural Network Study: Motivation, design, and initial feasibility analyses

Abstract: We introduce and describe the Reference Ability Neural Network Study and provide initial feasibility data. Based on analyses of large test batteries administered to individuals ranging from young to old, four latent variables, or reference abilities (RAs) that capture the majority of the variance in age-related cognitive change have been identified: episodic memory, fluid reasoning, perceptual speed, and vocabulary. We aim to determine whether spatial fMRI networks can be derived that are uniquely associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
121
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 32 publications
4
121
0
Order By: Relevance
“…In addition, any performance on tests in the cognitive test battery that was indicative of mild cognitive impairment was grounds for exclusion. More detailed description about this study can be found in (Salthouse et al, 2015; Stern et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, any performance on tests in the cognitive test battery that was indicative of mild cognitive impairment was grounds for exclusion. More detailed description about this study can be found in (Salthouse et al, 2015; Stern et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Age-related changes to mental processes occur across a host of different cognitive abilities ranging from fluid reasoning to perceptual speed (Braver & West, 2008; Craik & Byrd, 1982; Stern et al, 2014). Though many studies have investigated changes to brain structure across the life span (De Leon et al, 1997; Fischl & Dale, 2000; Fjell et al, 2006; Jack et al, 1997; Salat et al, 2004), and a number of studies have investigated the relationship between volumetric measures of brain integrity and cognition (see Kaup, Mirzakhanian, Jeste, & Eyler, 2011, for a recent review), relatively few studies have explored the relationship between cortical thickness and cognitive decline (c.f.…”
mentioning
confidence: 99%
“…In a previous paper (Stern et al, 2014), we introduced the Reference Ability Neural Network Study, which administers 12 cognitive neuroimaging tasks (3 for each RA) to healthy adults age 20–80 in order to derive unique neural networks underlying these 4 RAs and investigate how these networks may be affected by aging. We used a multivariate approach, linear indicator regression, to derive a unique covariance pattern or Reference Ability Neural Network (RANN) for each of the 4 RAs. The RANNs were derived from the neural task data of 64 younger adults of age 30 and below.…”
mentioning
confidence: 99%
“…In a previous paper (Stern et al, 2014), we introduced the Reference Ability Neural Network Study, which administers 12 cognitive neuroimaging tasks (3 for each RA) to healthy adults age 20–80 in order to derive unique neural networks underlying these 4 RAs and investigate how these networks may be affected by aging.…”
mentioning
confidence: 99%